Monitoring and groundwater/gas sampling in sands densified with explosives (2014)
This paper presents the results of a blast densification field study conducted at a waste disposal landfill located in South Carolina, United States, to determine the type of gases released and their in-situ concentrations in the ground after blast densification. The BAT probe system was used to collect groundwater and gas samples at the middle of the targeted layer and to measure the porewater pressure evolution during and after the detonation of the explosive charges. In addition, standard topographic surveys along the centerline of the tested zones were conducted after each blast event to quantify the effectiveness of the blast densification technique to densify loose sand deposits. The results of this study show that: a) the BAT probe system is a reliably in situ technique to collect groundwater and gas samples before and after blasting; b) the soil mass affected by the detonation of the explosives fully liquefied over a period of 6 hours while the in-situ vertical effective stresses returned to their initial values after about 3 days; and c) significant induced vertical strains were observed in the blasting area after each detonation, indicating that the soil mass has been successfully densified.